2014
DOI: 10.1002/2013gl058773
|View full text |Cite
|
Sign up to set email alerts
|

Strong chemistry‐climate feedbacks in the Pliocene

Abstract: The Pliocene epoch was the last sustained interval when global climate was significantly warmer than today but has been difficult to explain fully based on the external forcings from atmospheric carbon dioxide and surface albedo. Here we use an Earth system model to simulate terrestrial ecosystem emissions and atmospheric chemical composition in the mid-Pliocene (about 3 million years ago) and the preindustrial (~1750s). Tropospheric ozone and aerosol precursors from vegetation and wildfire are~50% and~100% hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 62 publications
(73 reference statements)
1
44
0
Order By: Relevance
“…Our work thus suggests that SOA reductions may have amplified regional warming in the present but minimized regional cooling at the LGM relative to the preindustrial. Results from these sensitivity studies, however, underscore the large uncertainties in current model estimates of SOA radiative forcing across long timescales (e.g., Scott et al, 2014;Unger and Yue, 2014;Unger, 2014a). Unlike SOA, we find that changes in tropospheric mean ozone burdens relative to the preindustrial are insensitive to the uncertainties in isoprene emissions and photochemistry tested in this study.…”
Section: P Achakulwisut Et Al: Uncertainties In Isoprene Photochemisupporting
confidence: 41%
“…Our work thus suggests that SOA reductions may have amplified regional warming in the present but minimized regional cooling at the LGM relative to the preindustrial. Results from these sensitivity studies, however, underscore the large uncertainties in current model estimates of SOA radiative forcing across long timescales (e.g., Scott et al, 2014;Unger and Yue, 2014;Unger, 2014a). Unlike SOA, we find that changes in tropospheric mean ozone burdens relative to the preindustrial are insensitive to the uncertainties in isoprene emissions and photochemistry tested in this study.…”
Section: P Achakulwisut Et Al: Uncertainties In Isoprene Photochemisupporting
confidence: 41%
“…in the size dependency, and by variations in the degree of passive vs. active uptake of CO 2 by the alkenone-producing coccolithophorids (Bolton and Stoll, 2013). Furthermore, van de Wal et al (2011) already showed that the relationship of CO 2 to temperature change during the last 20 Myr is opposite in sign for alkenone-based CO 2 than for other approaches.…”
Section: Detecting Any State Dependency In S [Co 2 Li]mentioning
confidence: 97%
“…CH 4 , N 2 O, or aerosols. For the Pliocene, strong chemistry-climate feedbacks have been proposed (Unger and Yue, 2014), suggesting high ozone and aerosol levels and potentially high CH 4 values. This implies that the relationship of CO 2 to other forcing agents might have been different for the cold climates of the late Pleistocene than for the warm climates of the Pliocene.…”
Section: Martínezmentioning
confidence: 99%
See 1 more Smart Citation
“…1), nor by a higher Earth System Sensitivity 10 to CO 2 forcing as suggested in an accompanying News & Views 13 . At its heart lies identifying mechanisms that can support weak temperature gradients 1,11 , which may be rooted in models' relatively weak meridional SST gradient reduction due to unresolved climate feedbacks [14][15][16] . The Pliocene puzzle becomes even more concrete when looking further back into the Early Pliocene (4-5Ma) as SST proxies from around the globe indicate a further weakening of SST gradients 1 , whereas constraining warm pool SST changes remains difficult since they fall within the uncertainty of paleo proxies.…”
mentioning
confidence: 99%